Uso da biodiversidade por populações humanas na caatinga e na Mata Atlântica, Rio Grande do Norte, Nordeste do Brasil - Torres, Denise de Freitas (2011)
The use of animals is a common activity but it can be really variable between human populations. This work analyzed the knowledge about useful animal species between human communities in Caatinga and Atlantic Forest considering the influence of socioeconomics and environmental factors on the species selection. Forty people were interviewed in Caraúbas community (Atlantic Forest) and thirty were interviewed in Barrocas community (Caatinga). A total of 193 animals were cited. The communities showed a low degree of similarity (20%) and the general diversity of mentioned species was significantly bigger in Caraúbas. Men cited a diversity of species greater than women for food category in Caraúbas and pet category in Caraúbas and Barrocas. Women cited greater species diversity for medicinal use in Caraúbas. In general, in both communities, the age group >60 years showed a greater knowledge than the others. The multiple regression analysis showed the age as the only socioeconomic factor which influenced significantly the knowledge about animals for the food category in both communities. Considering the richness of known species, there were differences only between gender for sum of uses and food category in Caraúbas and for the pet category in Barrocas with men showing a greater knowledge than women. The results showed that local environmental differences are fundamental at the species selection but they also showed that within communities there are other factors like gender and age that tend to influence the knowledge about species. It is important to consider cultural, economic, social and environmental factors to understand better the interactions between people and animals so that this information can be used to facilitate the implementation of conservation measures